Effect inhole-3-butyric acid (IBA) on cuttings Chromolaena odorata (growth and root development) - Ezza Fatin Jamaluddin (2011)
The study to evaluate the effects of indole-3-butyric acid (IBA) concentration i.e. 0, 500, 1000 and 2000 ppm to three types of cuttings (softwood, semi-hardwood and hardwood) on growth and root development of Chromolaena odorata. This study was conducted in Agropark, University Malaysia Kelantan. By using the completely randomized block design, cuttings were taken in areas around University Malaysia Kelantan and planted in the medium containing soil (60%), compost (20%) and sand (20%) after dipping in indole-3-butyric acid (IBA) for five minutes. Five different parameters were studied for number of leaves; branches and branch length were measured per week while number of root and root length were measured for four weeks interval. It was obvious that the root initiation of Chromolaena odorata is significantly (P <0.05) influenced by the interactive effect of cutting age and IBA concentration. Maximum number of leaves (19.13), branches (4.00), branch length (7.43), number of root (45.11), and root length (12.87) was obtained in cuttings treated with 2000 ppm while minimum number of leaves (12.6), branches (2.47), branch length (5.93), number of root (24.33), and root length (6.60), was recorded in control treatment. Meanwhile, the cuttings taken from softwood had higher number of leaves (19.30), branches (3.70), branch length (7.25), number of root (45.25), and root length (12.40) than those taken from semi-hardwood and hardwood. Softwood cutting responded more positively to IBA and stimulated leaf and root formation.